Spells - Gravett, Emily (New York : Macmillan, 2008)
A small green frog has a series of misadventures as he pursues his dream of kissing a princess.
Includes divided pages.
K-3.
Keywords: Frogs -- Juvenile fiction; Imagination -- Juvenile fiction; Toy and movable books -- Specimens; Frogs -- Fiction; Humorous stories; Imagination -- Fiction; Toy and movable books; Frogs -- Fiction; Humorous fiction; Imagination -- Fiction; Toy and movable books; Humorous fiction